Transforming Growth Factor-beta 1 (TGF-β1) as a Master Regulator of Diabetic Nephropathy in Patients with type-ll Diabetes attending Aswan University Hospital - Aly Mahmoud Obaed; Zain El-Abdeen Ahmed Sayed; Hala Mahmoud; Emad Farah Mohammed Kholef; Mohammed Mohiey El-Din Fouad; Abdallah Elebidi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Objective:The objective is to study type ll diabetic patients at Aswan University Hospital and determine the function of converting growth factor-beta 1 (TGF-β1) toward the development of diabetic kidney disease (DKD). Methods: We used a case-control design in this investigation. Our research includes 90 participants. The first group was the control group, which included healthy people randomly selected from the Aswan University Hospital blood bank.; second, there was the group of type 2 diabetics who did not have nephropathy; and third, there was the group of type 2 diabetics who did have nephropathy. The subjects for Groups 2 and 3 were sourced from the nephrology and diabetes clinics at Aswan University Hospital in Aswan, Egypt. Results: According to these findings, TGF-β1 may serve as an early and highly specific marker of diabetic neuropathy in individuals who have diabetes of the type 2 variety. In the Type 2 diabetes. with nephritis group, the mean TGF-β1 level was 1424.3 ± 95.8 ng/ml, which was substantially higher than in the controls group (392.5 ± 14.9, p<0.001) and the people with type 2 diabetes with no nephropathy group (523.3 ± 22.5, p<0.001). Similarly, the mean level was much higher (p=0.003) in the group of type 2 diabetics without nephropathy compared to the control group. Conclusion: Compared to adults without diabetes and healthy controls, those with diabetic neuropathy had considerably greater levels of TGF-β1. Moreover, T2DM cases without nephropathy group had significantly higher mean level than control. Furthermore, at the cutoff value of 435 ng/ml,; the TGF-β1 had better ability for prediction of T2DM with nephropathy as sensitivity 94%, specificity 87% PPV 88%, NPV 93.5% and overall, the test had 90.5% accuracy. Indicating that TGF-β1 has the potential to be a very sensitive and specific early indication of diabetic neuropathy in adults with type 2 diabetes.